2008
DOI: 10.1073/pnas.0804446105
|View full text |Cite
|
Sign up to set email alerts
|

The G-protein-coupled receptor kinase 5 inhibits NFκB transcriptional activity by inducing nuclear accumulation of IκBα

Abstract: G-protein-coupled receptor (GPCR) kinases, GRKs, are known as serine/threonine kinases that regulate GPCR signaling, but recent findings propose functions for these kinases besides receptor desensitization. Indeed, GRK5 can translocate to the nucleus by means of a nuclear localization sequence, suggesting that this kinase regulates transcription events in the nucleus. To evaluate the effect of GRK5-IB␣ interaction on NFB signaling, we induced the overexpression and the knockdown of GRK5 in cell cultures. GRK5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
143
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 107 publications
(152 citation statements)
references
References 51 publications
8
143
1
Order By: Relevance
“…In recent years, we and others have confirmed that endothelin (15), ␤-and ␣-adrenergic (17, 23), prostaglandin E 2 (24) receptors, in addition to the signaling molecules associated with many GPCRs, including adenylate cyclase (25), G-protein coupled receptor kinases (GRK) (26,27), phospholipase proteins (22), G i , G s , and G q , are present on the nuclear/perinuclear membranes in a constitutive manner, independent of agonist stimulation. Determining the subcellular localization of proteins provides crucial information concerning their function and interaction with other molecules in a specific microenvironment, and thus represents a critical step in genome annotation.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, we and others have confirmed that endothelin (15), ␤-and ␣-adrenergic (17, 23), prostaglandin E 2 (24) receptors, in addition to the signaling molecules associated with many GPCRs, including adenylate cyclase (25), G-protein coupled receptor kinases (GRK) (26,27), phospholipase proteins (22), G i , G s , and G q , are present on the nuclear/perinuclear membranes in a constitutive manner, independent of agonist stimulation. Determining the subcellular localization of proteins provides crucial information concerning their function and interaction with other molecules in a specific microenvironment, and thus represents a critical step in genome annotation.…”
Section: Discussionmentioning
confidence: 99%
“…11 The antibodies anti-IB␣, actin, and histone 3 were from Santa Cruz Biotechnology, Inc; anticleaved caspase 3, NF-B, p-NFB (p65), and phospho-cAMP responsive element binding (p-CREB) antibodies were from Cell Signaling Technology. Densitometric analysis was performed using Image Quant software (Molecular Dynamics, Inc).…”
Section: Western Blotmentioning
confidence: 99%
“…In H9C2 cardiomyoblasts, AdGRK5-NT caused an increase of total IB␣ levels ( Figure 1A), analyzed by Western blot, as described previously in other cellular types. 11,12 The effect of GRK5-NT on NF-B activity was evaluated by luciferase assay. PE increased NF-B transcription activity, and the overexpression of GRK5-NT reduced such effect both in basal conditions and after PE stimulation ( Figure 1B), suggesting that NF-B is induced by hypertrophic stimuli in cardiac cells and that GRK5-NT is able to inhibit such phenomenon.…”
Section: In Vitro Studymentioning
confidence: 99%
See 2 more Smart Citations